The prevalence and risk factors of posttraumatic cerebral infarction in patients with traumatic brain injury: a systematic review and meta-analysis. Issue 5 (2nd May 2022) - Zhi-Ling, Chen; Qi, Li; Jun-Yong, Yang; Bang-Qing, Yuan
ABSTRACT: Posttraumatic cerebral infarction (PTCI) is a serious complication of traumatic brain injury (TBI), and the prevalence and risk factors of PTCI in TBI patients are in dispute. We systematically searched the literature in the PubMed, Embase, and Cochrane library up to October 2021 to identify studies on the prevalence and risk factors of PTCI in patients with TBI. The quality of observational studies was assessed by the Newcastle–Ottawa scale tool. Random-effects model was conducted. The Higgins` I 2 statistic was used to measure heterogeneity between trials. Moreover, sensitive analyses were conducted to assess whether the pooled result was credible and robust. Eleven studies (3696 total TBI patients) were included. The pooled prevalence of PTCI in TBI patients was 14% (95% CI, 0.11–0.17; I 2 = 83.1%). Sensitive analyses showed that the pooled prevalence of PTCI was 13% (95% CI, 0.10–0.15; I 2 = 69.2%) by omitting Su et al. The prevalence of PTCI was associated with a lower Glasgow Coma Scale (GCS) score (OR, 0.33; 95% CI, 0.14–0.77; I 2 = 99.2%), pupillary dilation (OR, 4.73; 95% CI, 4.30–5.19; I 2 = 85.6%), abnormal PT (OR, 1.16; 95% CI, 1.05–2.47; I 2 = 99.2%), hematoma location (OR, 1.16; 95% CI, 1.05–2.47; I 2 = 99.2%) and hematoma volume (OR, 1.16; 95% CI, 1.05–2.47; I 2 = 99.2%). Whereas hypotensive shock, duraplasty, cerebral herniation, and thrombocytopenia were not statistically associated with PTCI. Lower GCS, pupillary dilation, abnormal PT, hematoma location, and hematoma volume were risk factors for PTCI. Considering some limitations, the conclusion of our study should be interpreted with caution. graphical abstract: uf0001